Biodiversity mediates relationships between anthropogenic drivers and ecosystem services across global mountain, island and delta systems. (January 2023) - Reader, Martin Oliver; Eppinga, Maarten B.; de Boer, Hugo Jan; Damm, Alexander; Petchey, Owen L.; Santos, Maria J.
Highlights: Biodiversity mediates many anthropogenic-ecosystem service relations. Species richness weakens more associations, whereas intactness amplifies more. Climate change had most weakened associations, population the most amplified. Abiotic, biotic and anthropogenic drivers are important to ecosystem service level. Biodiversity interactions are strongest in mountains and weakest in deltas. Abstract: Global change increasingly threatens nature, endangering the ecosystem services human wellbeing depends upon. Biodiversity potentially mediates these impacts by providing resilience to ecosystems. While biodiversity has been linked to resilience and ecosystem service supply on smaller scales, we lack understanding of whether mediating interactions between biodiversity and anthropogenic drivers are global and ubiquitous, and how they might differ between systems. Here, we examine the potential for biodiversity to mediate anthropogenic driver-ecosystem service relationships using global datasets across three distinct systems: mountains, islands and deltas. We found that driver-ecosystem service relationships were stronger where biodiversity was more intact, and weaker at higher species richness, reflecting the negative correlation between intactness and richness. Mediation was most common in mountains, then islands, then deltas; reducing with anthropogenic impact. Such patterns were found across provisioning and regulating ecosystem services, and occurred most commonly with climate change and built infrastructure. Further, we investigated the contribution of biodiversity and abiotic and anthropogenic drivers to ecosystem services. Ecosystem service supply was associated with abiotic and anthropogenic drivers alongside biodiversity, but all drivers were important to different ecosystem services. Our results empirically show the importance of accounting for the different roles that biodiversity plays in mediating human relationships with nature, and reinforce the importance of maintaining intact biodiversity in ecosystem functioning.